2022
DOI: 10.1007/s00018-022-04644-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of peripheral immune cells in spinal cord injury

Abstract: Secondary spinal cord injury is caused by an inflammatory response cascade, and the process is irreversible. The immune system, as a mediator of inflammation, plays an important role in spinal cord injury. The spinal cord retains its immune privilege in a physiological state. Hence, elucidating the mechanisms by which peripheral immune cells are recruited to the lesion site and function after spinal cord injury is meaningful for the exploration of clinical therapeutic targets. In this review, we provide an ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Inflammatory indicators were observed after 1 week since lymphocyte and macrophage aggregation occurred mainly at 1 week. 4 Only a few activated T cells were detected in the normal spinal cord, and a large number of CD25 + activated T cells (0.53 ± 0.14) were detected at the injury area after SCI, predicting the initiation of specific immunity (Figure 6A,C). In contrast to the P/G scaffolds (0.4 ± 0.12) and P/G-Met scaffolds (0.45 ± 0.06) which did not interfere with T cell activation, the P/G-CD80 mAb scaffolds (0.15 ± 0.04) and P/G-Met-CD80 mAb scaffolds (0.15 ± 0.05) significantly inhibited T cell proliferation and activation on account of the released CD80 mAb blocking the costimulatory signal.…”
Section: Scaffolds On Sci Ratsmentioning
confidence: 97%
“…Inflammatory indicators were observed after 1 week since lymphocyte and macrophage aggregation occurred mainly at 1 week. 4 Only a few activated T cells were detected in the normal spinal cord, and a large number of CD25 + activated T cells (0.53 ± 0.14) were detected at the injury area after SCI, predicting the initiation of specific immunity (Figure 6A,C). In contrast to the P/G scaffolds (0.4 ± 0.12) and P/G-Met scaffolds (0.45 ± 0.06) which did not interfere with T cell activation, the P/G-CD80 mAb scaffolds (0.15 ± 0.04) and P/G-Met-CD80 mAb scaffolds (0.15 ± 0.05) significantly inhibited T cell proliferation and activation on account of the released CD80 mAb blocking the costimulatory signal.…”
Section: Scaffolds On Sci Ratsmentioning
confidence: 97%
“…10−12 Soon after the primary injury, resident microglia are activated and immune cells including neutrophils and monocytes as well as macrophages are also recruited and infiltrated into the lesion sites. 9 Along with this, the inflammatory factors are oversecreted and the hyper inflammatory reactions occurred. 13 Besides, exaggerated inflammation promotes the process of oxidative stress due to the overproduction of oxidizing substances containing reactive nitrogen and oxygen species (RNOS), which further attack polyunsaturated fatty acids and trigger lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In the secondary injury of SCI, inflammation and oxidative stress as two pivotal cascades have been extensively documented. Soon after the primary injury, resident microglia are activated and immune cells including neutrophils and monocytes as well as macrophages are also recruited and infiltrated into the lesion sites . Along with this, the inflammatory factors are oversecreted and the hyper inflammatory reactions occurred .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the major role of Tregs in limiting inflammation-dependent damage in the spinal cord tissue has been previously reported [ 28 ]. These immunomodulatory roles are achieved due to the production of anti-inflammatory cytokines such as interleukin 10 (IL-10); the cell death promotion of cytotoxic T cells; or the sequestering of different proinflammatory cytokines from the environment, such as IL-2 [ 29 ]. In animal models of SCI, studies have demonstrated that increasing the amount of Tregs can enhance tissue healing and functional recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Treg cells can favorably influence the function of different glial cells after SCI. For instance, they can promote differentiation and migration of oligodendrocyte precursor cells (OPCs), leading to remyelination by oligodendrocytes; blockade of neurotoxic activation of the astroglia; and enhancing phagocytosis of myelin debris or reducing pyroptosis in microglial cells [ 29 ].…”
Section: Introductionmentioning
confidence: 99%